Brooklyn nine-nine. Season six [videorecording (DVD)] - Lampassi, Giovani; Carrillo, Cortney; Samberg, Andy, 1978-; Samberg, Andy, 1978-; Beatriz, Stephanie; Crews, Terry, 1968- (Universal Pictures Home Entertainment, 2019)
Follows the adventures of the detectives and their commanding officer in a Brooklyn, New York, police precinct.